Contrastes intra-urbains de la fécondité bruxelloise - Mathieu Buelens (Brussels Studies, 2021)
Few studies consider fertility variations on a detailed spatial scale. By considering both the intensity (the number of children born) and the timing of fertility (the age of the mother when she gives birth), the analysis presented here provides an overview of reproductive trends in Brussels. As individual factors such as income level influence fertility patterns, the geography of these patterns points to major intra-urban socio-spatial contrasts, and also tends to show the influence of contextual factors which remain to be studied.